Navigating the water trilemma: a strategic assessment of long‐term national water resource management options for Great Britain. (2nd May 2018) - Ives, Matthew C.; Simpson, Mike; Hall, Jim W.
Abstract: Potential increases in water demand, alongside uncertainties in water availability due to climate change, mean that Britain's water supply system could become increasingly stressed over the coming decades. Along with the need for secure water supplies, we must ensure that the supply is affordable and that sufficient water is available to safeguard the natural environment. Meeting these three separate goals of security, affordability and sustainability, with their inevitable trade‐offs, can be termed the 'water trilemma'. In this novel approach we simulate projections of river flows under population and climate change by using an aggregated national water resource model to test potential policies to manage demand and investments in water supply infrastructure in order to assess Britain's ability to meet its needs into the future. The results indicate that a balanced approach which allows for some inter‐basin water transfers while also engaging local solutions, including water re‐use, combined with scalable actions for demand management and leakage reduction, will best enable Britain to navigate this water trilemma.